(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Green computing is the study and practice of using computing resources efficiently. It aims to reduce the use of hazardous materials, maximize energy efficiency during the product’s lifetime, and promote recyclability or biodegradability of defunct products and factory waste. The plan towards green IT should include new electronic products and services with optimum efficiency.Â Green computing strategies can help us to build a safe place for us to live in .If each one of us becomes successful in constructing a healthy environmental balcony for ourselves then trust us we can together make our mother earth a healthy and a happy place for us to survive here.